Case report: BCR-ABL-positive acute lymphoblastic leukemia with bone destruction: a treatment dilemma - Lijun, Shi; Zhongrui, Ma; Li, Wei; Xia, Yu; Wei, Jiang; Yaning, Pan (Frontiers in Oncology, 2024)
Although bone destruction and hypercalcemia without acute peripheral blast BCR-ABL-positive acute lymphoblastic leukemia (ALL) have been reported in children, they are rare in adults. Herein, we describe a case of BCR-ABL positive ALL with a triploid karyotype, WT1, and CDKN2A mutations with hypercalcemia and bone destruction as the first manifestations. Complete remission (CR) was achieved by induction chemotherapy. BCR-ABL turned negative after treatment with dasatinib. However, computed tomography and whole-body bone scan showed extensive bone destruction. Additionally, bone biopsy showed leukemic infiltration. After treatment with dasatinib and VMCP, leukemia recurred with positive BCR-ABL. The T315I mutation occurred. The patient was surgically diagnosed with calculous cholecystitis and achieved CR2 by postoperative orebatinib and VP regimens. Later, the patient died due to a severe pulmonary infection. BCR-ABL-positive ALL with bone destruction is rare and difficult to control using tyrosine kinase inhibitor chemotherapy alone. Therefore, further exploration of more effective treatments is needed.